Pharmacological targeting of the HIF hydroxylases – A new field in medicine development. (February 2016) - Chan, Mun Chiang; Holt-Martyn, James P.; Schofield, Christopher J.; Ratcliffe, Peter J.
Abstract: In human cells oxygen levels are 'sensed' by a set of ferrous iron and 2-oxoglutarate dependent dioxygenases. These enzymes regulate a broad range of cellular and systemic responses to hypoxia by catalysing the post-translational hydroxylation of specific residues in the alpha subunits of hypoxia inducible factor (HIF) transcriptional complexes. The HIF hydroxylases are now the subject of pharmaceutical targeting by small molecule inhibitors that aim to activate or augment the endogenous HIF transcriptional response for the treatment of anaemia and other hypoxic human diseases. Here we consider the rationale for this therapeutic strategy from the biochemical, biological and medical perspectives. We outline structural and mechanistic considerations that are relevant to the design of HIF hydroxylase inhibitors, including likely determinants of specificity, and review published reports on their activity in pre-clinical models and clinical trials.